A Meta-Analysis of Systemic Evaluation of Knee Ligament Injury or Intervention of Knee Proprioceptive Function Recovery. (17th February 2022) - Zou, Longqiang; Yang, Yibin; Wang, Yihai
Abstract : Objective . The knee ligaments, as a passive knee joint stability device, provide protection for the knee joint and ensure its functional integrity. This role has long been known and recognized by people. The original purpose of knee ligament reconstruction after knee ligament injury is to restore its anatomical structure and mechanical stability mechanism. Methods . Taking athletes as the research object, randomized controlled trials (RCTs) on improving ankle joint function of athletes related to proprioception training at home and abroad were included. The search time was from the establishment of the database to December 31, 2019, and the references of related documents were traced. Two researchers independently screened the literature, extracted data, and evaluated the quality of the literature. RevMan 5.3 software was used for data analysis. Results . The extensor strength, flexor strength, and flexor strength/extensor strength of the affected limb were higher than before the operation one year after surgery (P < 0.01 ). The Lysholm score, Lysholm instability score, and one-foot jump distance were all higher than those before surgery (P < 0.05 ); the difference of KT-2000 for both knees was smaller than that before surgery (P < 0.05 ). Conclusion . In maintaining the anterior stability of the knee joint, the knee ligament provides 85% static resistance to prevent the tibia from moving forward, so knee ligament injury will cause knee instability. The proprioceptive feedback mechanism plays an important role in maintaining the functional stability of joints.